PAUPAR lncRNA suppresses tumourigenesis by H3K4 demethylation in uveal melanoma. Issue 12 (7th June 2016) - Ding, Xia; Wang, Xi; Lin, Ming; Xing, Yue; Ge, Shengfang; Jia, Renbing; Zhang, He; Fan, Xianqun; Li, Jin
Abstract : Uveal melanoma (UM) is the most common primary intraocular tumour in adults and has a high incidence. Nearly 50% of patients with UM develop metastases after diagnosis. Long noncoding RNAs (lncRNAs) are involved in both oncogenic and tumour suppression pathways. We show that lncRNA PAUPAR is present at low levels in UM tissues and cell lines and modulates the tumourigenesis of UM in vitro and in vivo . The ectopic expression of PAUPAR in UM cells revealed that PAUPAR acts as a necessary UM suppressor and induces the silencing of HES1 expression, which significantly reduces tumour metastasis. Mechanistically, PAUPAR modulates HES1 expression by inhibiting histone H3K4 methylation. These data support a role of this lncRNA as a novel therapeutic target in cancer prevention and treatment. Abstract :